2014
DOI: 10.1186/s13006-014-0025-2
|View full text |Cite
|
Sign up to set email alerts
|

Prelacteal feeding practices and associated factors among mothers of children aged less than 24 months in Raya Kobo district, North Eastern Ethiopia: a cross-sectional study

Abstract: BackgroundThe harmful infant feeding practices of prelacteal feeding is widely practiced in Ethiopia. Hence, it is vital to appreciate the cultural basis and potential factors on infant feeding practices in different parts of Ethiopia. This study aimed to investigate prelacteal feeding practices and associated factors among mothers of children aged less than 24 months in Raya Kobo district, North Eastern Ethiopia.MethodsA quantitative community-based cross-sectional study supplemented by qualitative methods wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
127
6
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(164 citation statements)
references
References 19 publications
25
127
6
6
Order By: Relevance
“…PLF has, also, been associated with a fourfold increased risk in infant deaths from infectious diseases [10]. Several studies have found that socio-economic conditions, lack of knowledge and cultural beliefs may contribute to PLF [1113]. …”
Section: Introductionmentioning
confidence: 99%
“…PLF has, also, been associated with a fourfold increased risk in infant deaths from infectious diseases [10]. Several studies have found that socio-economic conditions, lack of knowledge and cultural beliefs may contribute to PLF [1113]. …”
Section: Introductionmentioning
confidence: 99%
“…5,6 The most common reasons stated for PLF are insufficient milk production, advice from elders, family custom, assumption that it is good for health (child will talk early and tongue will become thin), to remove meconium from the gut of the child, and to prevent "evil eye" and illness. 5,7 The main risk factors associated with PLF practice include home delivery, lack of awareness of the risks associated with PLF, late initiation of breast-feeding, and influence by friends and relatives to give prelacteal feeds for their newborn. 5,6 There are limited studies conducted on this topic in Ethiopia.…”
mentioning
confidence: 99%
“…5,7 The main risk factors associated with PLF practice include home delivery, lack of awareness of the risks associated with PLF, late initiation of breast-feeding, and influence by friends and relatives to give prelacteal feeds for their newborn. 5,6 There are limited studies conducted on this topic in Ethiopia. Even the studies conducted on this and related topics show inconsistencies among their findings.…”
mentioning
confidence: 99%
See 2 more Smart Citations